Optimal timing of antenatal corticosteroid administration and preterm neonatal and early childhood outcomes - Battarbee, Ashley N.; Ros, Stephanie T.; Esplin, M. Sean; Biggio, Joseph; Bukowski, Radek; Parry, Samuel; Zhang, Heping; Huang, Hao; Andrews, William; Saade, George; Sadovsky, Yoel; Reddy, Uma M.; et al. (American journal of obstetrics & gynecology MFM, 2020)
Antenatal corticosteroids reduce morbidity and mortality among preterm neonates. However, the optimal timing of steroid administration with regard to severe neonatal and early childhood morbidity is uncertain. To evaluate the association between the timing of antenatal corticosteroid administration and preterm outcomes. We hypothesized that neonates exposed to antenatal corticosteroids 2 to <7 days before delivery would have the lowest risks of neonatal and childhood morbidity. Secondary analysis of 2 prospective multicenter studies enriched for spontaneous preterm birth, Genomics and Proteomics Network for Preterm Birth Research (11/2007–1/2011) and Beneficial Effect of Antenatal Magnesium (12/1997–5/2004). We included women with singleton gestations who received antenatal corticosteroids and delivered at 23 0/7 to 33 6/7 weeks’ gestation. Women who received ≥1 course of corticosteroids were excluded. Neonatal outcomes were compared by the timing of the first dose of antenatal corticosteroids in relation to delivery: <2 days, 2 to <7 days, 7 to <14 days, and ≥14 days. The primary outcome was respiratory distress syndrome. Secondary outcomes included composite neonatal morbidity (death, intraventricular hemorrhage grade III or IV, periventricular leukomalacia, bronchopulmonary dysplasia, or necrotizing enterocolitis) and early childhood morbidity (death or moderate to severe cerebral palsy at age 2). Multivariable logistic regression estimated the association between timing of antenatal corticosteroid administration and study outcomes. A total of 2259 subjects met inclusion criteria: 622 (27.5%) received antenatal corticosteroids <2 days before delivery, 821 (36.3%) 2 to <7 days, 401 (17.8%) 7 to <14 days, and 415 (18.4%) ≥14 days. The majority (78.1%) delivered following idiopathic spontaneous preterm labor or preterm prelabor rupture of membranes at a mean gestational age of 29.5 ± 2.8 weeks. Neonates exposed to antenatal corticosteroids 2 to <7 days before delivery were the least likely to develop respiratory distress syndrome (51.3%), compared to those receiving antenatal corticosteroids <2 days, 7 to <14 days, and ≥14 days before delivery (62.7%, 55.9%, and 57.6%, respectively, P < .001). Compared to receipt 2 to <7 days before delivery, there was an increased odds of respiratory distress syndrome with receipt of antenatal corticosteroids <2 days (adjusted odds ratio 2.07, 95% confidence interval 1.61–2.66), 7 to <14 days (adjusted odds ratio 1.40, 95% confidence interval 1.07–1.83), and ≥14 days (adjusted odds ratio 2.34, 95% confidence interval 1.78–3.07). Neonates exposed to antenatal corticosteroids ≥14 days before delivery were at increased odds for severe neonatal morbidity (adjusted odds ratio 1.57, 95% confidence interval 1.12–2.19) and early childhood morbidity (adjusted odds ratio 1.74, 95% confidence interval 1.02–2.95), compared to those exposed 2 to <7 days before delivery. There was no significant association between antenatal corticosteroid receipt <2 days or 7 to <14 days and severe neonatal morbidity or severe childhood morbidity. Preterm neonates exposed to antenatal corticosteroids 2 to <7 days before delivery had the lowest odds of respiratory distress syndrome, compared to shorter and longer time intervals between steroid administration and delivery. Antenatal corticosteroid administration ≥14 days before delivery is associated with an increased odds of severe neonatal and childhood morbidity, compared to 2 to <7 days before delivery. These results emphasize the importance of optimally timed antenatal corticosteroids to improve both short- and long-term outcomes.